(3GdeLGdS GdSfjI aj TQM GdCQHYjf GdfhhjIs - (3GHf CMeO Hf MLGRj GdaTfjs; (3jMji Hf TQa Hf oepqQj Hf MSf GdMRGej GdMhQGfj, Gdfhhj, GdTGaYqj, CHh RcQjG, eMjj GdOjf,J (B676 (3g` s ((3GdSjO eMehO Hf GdSjO MSjf GdHZOGOj s)
(3ChdgG (B:s
(3hHYO ajbhd GdabjQ Edi QMeI QHg GdZfj CMeO Hf MLGRj GdaTfj gPg eLGdS SfjI aj GdcdGe Ydi GdCQHYjf GdfhhjI s
(3BNQgG (B:s
(3hbGd HYVge HjfeG CfG aj SjGMJj hEPG HUhJ CSeYg hdG CQi TNUg jbhd jG YHGO Gddg Ef GdLfI QNjUI JeJ GdeMGSf GdSfjg aj GdCQHYjf GdfhhjI HMeO Gddg hYhfg s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdMOjK h GdeUWdMs